2019
DOI: 10.1136/bmjopen-2019-033827
|View full text |Cite
|
Sign up to set email alerts
|

A structured medication review tool to promote psychotropic medication optimisation for adults with intellectual disability: feasibility study

Abstract: ObjectivesTo investigate the feasibility of delivering structured psychotropic medication review in community services for adults with intellectual disability (ID).DesignSingle-arm feasibility study conducted over a 6-month period.SettingSpecialist community ID teams in England.ParticipantsPsychiatrists working with adults with ID and adults with ID who had been prescribed psychotropic medication.InterventionA structured web-based psychotropic medication review tool (the HealthTracker-based structured medicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Eight papers referenced the NICE guidelines in the introduction and/or discussion and often in support of the rationale for the research [ 2 , 17 , 28 , 35 , 37 , 45 , 61 , 62 ]. The NICE guidelines emphasize that antipsychotic medications should not be used to treat problem behaviour unless other non‐pharmacological approaches have been tried and failed and the person with ID or others are at serious risk of harm.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eight papers referenced the NICE guidelines in the introduction and/or discussion and often in support of the rationale for the research [ 2 , 17 , 28 , 35 , 37 , 45 , 61 , 62 ]. The NICE guidelines emphasize that antipsychotic medications should not be used to treat problem behaviour unless other non‐pharmacological approaches have been tried and failed and the person with ID or others are at serious risk of harm.…”
Section: Resultsmentioning
confidence: 99%
“…Fourteen studies describing dose reduction or cessation of psychotropic medications were identified [ 2 , 17 , 41 , 43 , 61 , 65–73 ] with one of these being a systematic review [ 17 ]. Two papers produced medication review tools for use by healthcare professionals [ 62 , 74 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Precision medicine is currently considered the future (and in part also the best present form) of psychiatric medicine practice for both inpatients and outpatients (Hampel et al, 2023; Keshavan and Clementz, 2023). The proposed interventions that would move current practice closer to the stated goals of precision medicine are many and varied, but therapy personalisation and optimisation are among the most important ones (Sheehan et al, 2019; De Leon, 2021). Both of these goals can be achieved by the implementation of suitable therapeutic drug monitoring (TDM) practices (Mandrioli et al, 2020), with the determination of drug and metabolite levels at regular intervals, their comparison to established or tentative reference ranges for efficacy or toxicity or both, and the execution of clinical decisions on drug posology and drug choice based on those chemical-clinical correlations (CCC) (Qu et al, 2022; Mercolini et al, 2023).…”
mentioning
confidence: 99%